Bacterial Profile and Antibiotic Susceptibility Pattern of Patients at Pre- and Post-Urologic Endoscopy Procedures at Prof. Dr. R. D. Kandou Hospital, Manado, Indonesia - Oroh, Paulus; Astram, Ari; Toreh, Christof; Arianto, Eko; Wihono, Frendy; Wariki, Windy; Raranta, Hessyani (e-CliniC, 2022)
Abstract: Development of antibiotics resistance condition has been at a concerning state while data on the distribution of bacterial profile and the incidence of resistances in Indonesia are currently still limited at hospital environment, including at Prof. Dr. R. D. Kandou Hospital in Manado, Indonesia. This study aimed to obtain the profile of bacteria and the pattern of susceptibility to antibiotics in patient’s urine before and after urologic endoscopy procedures at RSUP Prof. Dr. R. D. Kandou. This was an observational study with a cross sectional design. Sampling was performed with the one-group test technique of Lemeshow. The data collection technique used urine culture test by calculating the percentages. The results obtained 42 patients as subjects. The urinary bacterial profile of patients who underwent urologic endoscopy procedures at Prof. Dr. R. D. Kandou Hospital were dominated by Gram-negative bacteria, namely E. coli (23.8%), Klebsiella (4.8%), Acinetobacter baumannii (2.4%); 69% of urine samples showed negative culture results. The susceptibility pattern of bacteria to antibiotics in the subjects’ urine showed 100% sensitivity to the given antibiotics. No nosocomial infection was found, however, nosocomial infection yet could not be excluded. In conclusion, bacteria found in the patients’ urine are dominated by Gram-negative bacteria namely Escherichia coli, Klebsiella, and Acinetobacter baumannii which are still sensitive to antibiotics. Most urine samples showed negative results, and no nosocomial infection was found. Keywords: bacterial profile; bacterial susceptibility; antibiotic; urological endoscopic procedure